Synthesis of automatic control models - Райчев, І. Е. (Proceedings of National Aviation University (archive), 2021)
he question of the use of finite automata for processing information of parametric onboard registrars is considered. The analysis of the stages of synthesis of finite automata, depicting the algorithms of aircraft flight control